Partially Ordered Group of the 2×2 Symmetric Matrices - Irmatul Hasanah (Department of Mathematics, Faculty of Sciences and Technology, UIN Syarif Hidayatullah, 2019)
AbstractThis paper deals with the partially ordered group of the 2×2 symmetric matrices. A matrix is defined to be a positive if each entry of the matrix is positive. With the characterization of the 2×2 symmetric matrix, we construct the positive cone such that the set of the matrices constructs partially ordered group.Keywords: Symmetric Matrix, Group-Ordered, Positive Cone. AbstrakArtikel ini membahas grup terurut parsial pada matriks simetri berukuran 2×2. Suatu matriks dikatakan positif jika setiap entri pada matriks bernilai positif. Melalui karakteristik dari matriks simetri, akan dikonstruksi sebuah positif cone sehingga matriks simetri berukuran 2×2 merupakan grup terurut parsial.Kata kunci: Matriks Simetri, Grup Terurut, Positif Cone.